O serviço especializado de saúde e medicina do trabalho de guarulhos e as políticas de intervenção em saúde mental do trabalhador - Vechia, Patricia Rosin Lacintra [UNIFESP] (2014)
Under a global productive restructuration which its production model brings as consequence privatizations, unemployment and social exclusion, the worker have been losing his autonomy on your activities. In this reality, the contract employments takes place and the work relationships are unstable. In despite of that stem an illness, related to established work relationships and under the work environment. As consequence psychosocial repercussions caused by the suffering, dissatisfaction and job competition has been raising. Regarding to this, nowadays, mental health is a very important subject related to work. Considering this background, was studied existence actions of the Government Worker Safety and Health Technical Division/Work Safety and Occupational Medicine Specialized Service of the Guarulhos City Hall, with the intention of understand your operation, mainly referring to mental health actuation of the City Health System Bureau. It is a qualitative research using as tool method: bibliography research, documental analysis, semi structured interviews and secondary data about secondary reasons of work absences. Finally can be affirmed that there is shortage of related public service, to Sesmt and its performance in Mental Health Studies. The Government Worker Safety and Health Technical Division/Work Safety and Occupational Medicine Specialized Service has your policy towards to the city worker?s health of the Guarulhos City Hall including City Health System Bureau ones and more specifically, the denominated program ?Work Organization intervention? under Government Worker Safety and Health Technical Division/Work Safety and Occupational Medicine Specialized Service responsibility, progress to beyond of legal actuation of Work Safety and Occupational Medicine Specialized Service because pursuit an actuation on preventing and supervising injuries related to city workers? mental health, despite of restrictions related with lack of labor and i Guarulhos City Hall by the time that there is a contingent that has, so far 21 thousand workers and 7 thousand only at City Health System Bureau.